Nonparametric Estimation of Labor Supply Functions Generated by Piece Wise Linear Budget Constraints - Sören Blomquist; Whitney Newey (Uppsala University, Department of Economics, 1997)
The basic idea in this paper is that labor supply can be viewed as a function of the entire budget set, so that one way to account non-parametrically for a nonlinear budget set is to estimate a nonparametric regression where the variable in the regression is the budget set. In the special case of a linear budget constraint, this estimator would be the same as nonparametric regression on wage and nonlabor income. Nonlinear budget sets will in general be charac-terized by many variables. An important part of the estimation method is a procedure to reduce the dimensionality of the regression problem. It is of interest to see if nonparametrically estimated labor supply functions support the result of earlier studies using parametric methods. We therefore apply parametric and nonparametric labor supply functions to calculate the effect of recent Swedish tax reform. Qualitatively the nonparametric and parametric labor supply functions give the same results. Recent tax reform in Sweden hasincreased labor supply by a small but economically important amount.
urn:nbn:se:uu:diva-2388
Keywords: C14; H24; J22; 330; Nonparametric estimation; labor supply; nonlinear budget constraints; tax reform